ACC deaminase‐producing rhizosphere bacteria modulate plant responses to flooding. (30th January 2017) - Ravanbakhsh, Mohammadhossein; Sasidharan, Rashmi; Voesenek, Laurentius A. C. J.; Kowalchuk, George A.; Jousset, Alexandre
Summary: Flooding events are predicted to increase over the coming decades, calling for a better understanding of plant responses to submergence. Specific root‐associated microbes alter plant hormonal balance, affecting plant growth and stress tolerance. We hypothesized that the presence of such microbes may modulate plant responses to submergence. We tested whether root‐associated bacteria producing the enzyme ACC (1‐aminocyclopropane‐1‐carboxylate) deaminase affect submergence responses in Rumex palustris, a flood‐tolerant riparian plant. Ethylene is a key plant hormone regulating flood‐associated acclimations, and ACC deaminase activity of bacteria may decrease ethylene levels in the plant. Rumex palustris plants were inoculated with Pseudomonas putida UW4 or an isogenic mutant lacking ACC deaminase, and subsequently exposed to complete submergence. Submergence triggered ethylene‐mediated responses, including an increase in leaf elongation and shoot fresh weight. Flood responses, including post‐submergence ethylene production, were reduced in plants inoculated with ACC deaminase‐producing wild type bacteria, as compared to plants inoculated with the ACC deaminase‐negative mutant. Synthesis . We demonstrate that root‐associated bacteria can alter plant response to environmental stress by altering plant hormonal balance. Plant–microbe interactions may thus be an overseen driver of plant life‐history strategies that should be taken into account when assessing plant ecological adaptations such as abiotic stress resistance. Abstract : We demonstrate that root‐associated bacteria can alter plant response to environmental stress by altering plant hormonal balance. Plant–microbe interactions may thus be an overseen driver of plant life‐history strategies that should be taken into account when assessing plant ecological adaptations such as abiotic stress resistance.